Development and Adaptation of Sports Facilities - Puglisi, Valentina (Recent Research Advances in Arts and Social Studies Vol. 6, 2024)
The sports facility is a powerful attractor and economic promoter able to give a significant boost to the enhancement of the surrounding urban fabric in full respect of the environment. The modern sports facility is a multipurpose and innovative structure from the point of view of both functionality and the materials and technologies used for its construction in large part of industrial origin, in order to ensure faster implementation at controlled and certain costs. A multipurpose structure that must be able to promote not only sporting events but many other types of events and host different types of users: fans, families, children, tourists, etc. The contribution of technology is a decisive factor here. To promote the construction of quality sports facilities it is essential to use the modern technical-financial tools developed by the world Real Estate as investment funds. Innovative and sophisticated financial instruments that operate in full compliance with current rules, subject to the supervision of the Bank of Italy and last but not least, that are able to collect the financial funds necessary for the realization of the work [1]. This text aims to illustrate the most interesting and innovative projects of sports facilities in progress in Italy and the actors and tools that made them possible, resulting from the encounter between the world of Real Estate and sports clubs in the various disciplines. In particular, the text analyses the technical, economic and financial arrangements that have made it possible to implement the projects, and the main problems that have been encountered. The research focuses on the comparison of some of the most important initiatives carried out at the European level in the field of improving sports facilities, with particular regard to the revenues generated by the stadium (subscriptions, catering, etc.) and the regulatory aspects (Stability Law 2014). The transition from the “cost system” model to that of the “revenue system” is one of the main goals still to be achieved by the Italian sports system. In recent years, there have been many factors that have slowed down this transition phase, starting with the complexity and length of the bureaucratic procedures required for implementing the various projects, as well as the actual difficulty for private and public stakeholders to invest in sports facilities [2].